Direct extraction of an empirical temperature-dependent InGaP - Raghavan, A.
A new empirical InGaP/GaAs heterojunction bipolar transistor (HBT) large-signal model including self-heating effects is presented. The model accounts for the inherent temperature dependence of the device characteristics due to ambient-temperature variation as well as self-heating. The model is accompanied by a simple extraction process, which requires only dc current-voltage (I-V) and multibias-point small-signal S-parameter measurements. All the current-source model parameters, including the self-heating parameters, are directly extracted from measured forward I-V data at different ambient temperatures. The distributed base-collector capacitance and base resistance are extracted from measured S-parameters using a new technique. The extraction procedure is fast, accurate, and inherently minimizes the average squared-error between measured and modeled data, thereby eliminating the need for further optimization following parameter extraction. This modeling methodology is successfully applied to predict the dc, small-signal S-parameter, and output fundamental and harmonic power characteristics of an InGaP/GaAs HBT, over a wide range of temperatures.
Keywords: HBT; InGaP-GaAs.; InGaP/GaAs.; Ambient-temperature variation; Average squared-error.; De current-voltage measurements; Distributed base-collector capacitance; Empirical temperature-dependent model; Extraction process; Forward I-V data; Harmonic power characteristics; Large-signal model; Multibias-point small-signal S-parameter measurements; Self-heating effects